INVESTIGATION OF APPLICABILITY OF PURE PROPANE GAS FOR MICRODOSIMETRY AT NEUTRON FIELDS: A MONTE CARLO STUDY. Issue 1 (20th December 2018) - Chattaraj, Arghya; Selvam, T Palani; Datta, D
Abstract: Applicability of pure propane gas for microdosimetric measurements in neutron fields was investigated using the FLUKA Monte Carlo code. Monoenergetic neutrons in the energy range 1 keV−20 MeV and the ISO-neutron sources such as 241 Am-Be, 241 Am-B, 252 Cf and 252 Cf + D2 O were considered in the present study. The tissue-equivalent proportional counter (TEPC) simulated in the study was LET-1/2 (by Far West Technology) with site sizes 1, 2 and 8 μm. The study demonstrates that for a given site size, the TEPC filled with tissue-equivalent propane and pure propane gases produce similar microdosimetric distributions when the density of pure propane gas is lowered appropriately. For the ISO-neutron sources, the density of propane gas requires scaling by a factor 0.85. For the monoenergetic neutrons, depending upon the neutron energy, the values of scaling factors are in the range of 0.58–0.93.